The RELATIONSHIP OF THE HEAD OF THE ROOMS SUPERVISION FUNCTION WITH NURSES COMPLIANCE IN HAND HYGIENE IN THE EMERGENCY INSTALLATION OF RATU ZALECHA MARTAPURA REGENCY HOSPITAL - Adisurya Saputra; Septian Mugi Rahayu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to determine the relationship between the supervisory function of the head of the room and the compliance of nurses in hand hygiene in the Emergency Room of Ratu Zalecha Martapura Hospital, Banjar Regency. Methods: this study uses correlational research with a cross-sectional design. The study population was all nurses in the Emergency Room at Ratu Zalecha Martapura Hospital, Banjar Regency, consisting of 24 people. Samples were taken by sampling technique using total sampling method. The research data were obtained from questionnaires and observation sheets, the data were analyzed through the Chi square statistical test. Results: from univariate analysis showed that the supervisory function of the head of the room was mostly in the good category (79.2%), while the compliance of nurses in hand hygiene was mostly in the obedient category (75%). The bivariate analysis showed that there was a significant relationship between the supervising function of the head of the room and the compliance of nurses in hand hygiene with a value of p = 0.001. Conclusion: Suggestion It is expected that the hospital will conduct in-house training on the importance of hand hygiene and carry out hand hygiene SOP at 5 moments according to WHO standards, it is necessary to carry out supervision and direction from the head of the room through communication with the implementing nurse to carry out hand hygiene in the inpatient room